MENSAGEM DOS DIRIGENTES - Friede, Reis; Azulay Neto, Messod; Araújo Filho, Luiz Paulo da Silva; Athié, Ivan (LexCult: revista eletrônica de direito e humanidades; v. 4 n. 1 (2020): Estado em Debate, 2020)
Mensagem dos Dirigentes.